Construction of compressible Polymer/MXene composite foams for high-performance absorption-dominated electromagnetic shielding with ultra-low reflectivity. (March 2021) - Jia, Xichen; Shen, Bin; Zhang, Lihua; Zheng, Wenge
Abstract: The conductive polymer composite (CPC) foams are always accompanied with obvious reflection of EM waves during electromagnetic interference (EMI) shielding, and the significant reduction of EM reflection via structural design of CPC foams to minimize the secondary EMI pollution is deemed very important. Herein, for preparing designable MXene-based CPC foams with high-efficiency EMI-shielding performance and ultra-low reflectivity, novel MXene-decorated polymer foam beads (MPFBs) were fabricated to serve as building blocks by the assistance of polyaniline (PANI), and CPC foams were constructed by assembling MPFBs into 3D accumulation with MXene networks followed by the encapsulation of polydimethylsiloxane (PDMS), which presented superb EMI SE of ∼23.5–39.8 dB with only ∼0.0225–0.0449 vol% MXene (plus ∼0.02 vol% PANI), along with low R coefficient of ∼0.20–0.31. By further employing the asymmetric gradient configuration, ultra-low R coefficient of ∼0.05 was obtained with effective EMI SE of ∼23 dB at total MXene content of only ∼0.0225 vol%, which is the lowest R values for effective EMI shields ever reported. In addition, because of their remarkable compressibility, convenient SE regulation of PDMS/MPFB composite foams by mechanical compression was demonstrated, showing a function to switch between inefficient shielding of SE < 20 dB and effective shielding of SE > 20 dB. Graphical abstract: Image 1